THE EFFICIENCY OF TEACHING ACTIVITY THROUGH REFLECTIVE PRACTICE - Emil LAZĂR (Universitaria Publishing House, Craiova, 2022)
Reflective practice is a valuable resource, still underexploited, which can bring important benefits to the teacher and, implicitly, to the pupils, ensuring school success and, subsequently, professional and social. Reflective action involves the desire to engage in self-assessment and selfdevelopment, which must become constants of the professional practice of the teacher. It also requires flexibility from teachers, rigorous analysis and awareness of the impact and effectiveness of their own work in relation to the specifics and beneficiaries of its work, students. This study is about teachers' awareness of the fact that the continuous improvement of the quality of the educational process involves, first of all, reflection on it. Reflective practice should become an intrinsic component of educational practices, a situation that requires the instrumentality of teachers with a set of knowledge and skills necessary for this endeavour, but also the development of a set of tools to assess the impact of the activity of didactic staff on the learning carried out by students, as an expression of its effectiveness. This research investigates respondents' opinions on the importance of knowing their own impact of teaching on school progress and student learning and aims to identify tools for measuring/ assessing the impact of teachers' activity on pupils and developing transversal skills on improving professional performance, self-control and reflective analysis of their own activity